7
$\begingroup$

Is the pullback of a covering map $p:E\rightarrow B$ along a continuous map $f:C\rightarrow B$ a covering map?

$\endgroup$
  • $\begingroup$ ..and I guess that (at least for nice topological spaces, where coverings are usually used) the pullback covering is the covering of $C$ corresponding to the kernel of $\pi_1(f) \,: \pi_1(C) \to \pi_1(B)$.. $\endgroup$ – fritz Feb 14 '17 at 15:12
5
$\begingroup$

Yes. Let $E^\prime=E\times_BC$ be the pullback with $p^\prime:E^\prime\rightarrow C$ the projection and $f^\prime:E^\prime\rightarrow E$ the other projection. Suppose $U\subseteq B$ is evenly covered by $p$, meaning that $p^{-1}(U)=\coprod_{i\in I}V_i$ with the $V_i$ open subsets of $E$, each of which is mapped homeomorphically onto $U$ by $p$. Then I claim that $f^{-1}(U)$, an open subset of $C$, is evenly covered by $p^\prime$. In fact, we have $(p^\prime)^{-1}(f^{-1}(U))=(f^\prime)^{-1}(p^{-1}(U))=\coprod_{i\in I}(f^\prime)^{-1}(V_i)$. So we need to check that each $(f^\prime)^{-1}(V_i)$ is mapped homeomorphically onto $f^{-1}(U)$ by $p^\prime$. But the restriction $p^\prime:(f^\prime)^{-1}(V_i)\rightarrow f^{-1}(U)$ is the pullback of the restriction $p:V_i\rightarrow U$ along $f:f^{-1}(U)\rightarrow U$, so because the restriction of $p$ is a homeomorphism, so is the restriction of $p^\prime$.

$\endgroup$
  • $\begingroup$ For further readers: homeomorphism comes from universal property of pullback along arrows $id_C|_{f^{-1}(U)}$ and $(p|_{V_i})^{-1} \circ f|_{f^{-1}(U)}$. $\endgroup$ – Stephen Dedalus Feb 26 '15 at 15:11
  • $\begingroup$ Why the pullback of the restriction $p : V_i \to U$ along $f:f^{-1}(U) \to U$is also homeomorphism? $\endgroup$ – ChoMedit Mar 27 '18 at 11:24
3
$\begingroup$

Yes. If $c \in C$, choose a n.h. $U$ of $f(c)$ such that the preimage $p^{-1}(U)$ of is a union of open subsets each mapping isomorphically to $U$. Then $f^{-1}(U)$ is a n.h. of $c$ with the analogous property (since the preimage of the pull-back over $f^{-1}(U)$ is the same as the pull-back of $p^{-1}(U) \to U$ via $f^{-1}(U) \to U$).

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.